A Semiotic Analysis on The Poem October by Louise Glück using Roland Barthes’ Theory: Psycholinguistic View - Siti Ithriyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Meaning of denotation and connotation is part of the semiotic aspect in analyzing a text or image. Barthes’ theory is the development of semiotics in the analysis of image objects. It is this reader who will bring up various perceptions of meaning. This meaning is the meaning of which exists at the first level of the semiotic system. While the meaning connotation is a subjective meaning that arises when we associate it with elements of the emotions and feelings of the readers with the cultural values they have. The meaning of this connotation is the second level of the semiotic system. To get the connotative meaning from the psychological aspect, it can also be used in analyzing a text, in this case poetry. This research uses content analysis and descriptive qualitative with describes about semiotic Barthes’ theory and attempts to explore the application of sentence from the poem October by Louise Glück. Researcher will collect the data from sentences on poem and analyzed it. The analyzed with psycholinguistic view so the researcher will explain about the definition of it and the relationship between the semiotic analysis of poetry symbols and the psychology of the author in the poem entitled October.